2016
DOI: 10.1001/jamapediatrics.2015.3210
|View full text |Cite|
|
Sign up to set email alerts
|

Use of Procalcitonin Assays to Predict Serious Bacterial Infection in Young Febrile Infants

Abstract: IMPORTANCE The procalcitonin (PCT) assay is an accurate screening test for identifying invasive bacterial infection (IBI); however, data on the PCT assay in very young infants are insufficient. OBJECTIVE To assess the diagnostic characteristics of the PCT assay for detecting serious bacterial infection (SBI) and IBI in febrile infants aged 7 to 91 days. DESIGN, SETTING, AND PARTICIPANTS A prospective cohort study that included infants aged 7 to 91 days admitted for fever to 15 French pediatric emergency depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
169
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(180 citation statements)
references
References 40 publications
2
169
6
1
Order By: Relevance
“…29 However, we do know that the youngest infants with fever are infrequently pretreated with antibiotics. 16,18 Sixth, EV PCR testing decisions were at the discretion of the clinical team. Although we adjusted for patient age and study year, and clustering by center, we cannot fully control for clinical differences between tested and untested infants, raising the potential for unadjusted confounding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 However, we do know that the youngest infants with fever are infrequently pretreated with antibiotics. 16,18 Sixth, EV PCR testing decisions were at the discretion of the clinical team. Although we adjusted for patient age and study year, and clustering by center, we cannot fully control for clinical differences between tested and untested infants, raising the potential for unadjusted confounding.…”
Section: Discussionmentioning
confidence: 99%
“…We defined an invasive bacterial infection as growth of pathogenic bacteria from blood or CSF culture. Serious bacterial infection (SBI) was defined by the presence of any invasive bacterial infection or a urinary tract infection (UTI) 16 defined as a catheterized urine culture with ≥50,000 colony-forming units (CFUs)/mL of a single pathogenic bacteria or 10,000–50,000 CFUs/mL of a single pathogenic bacteria with an abnormal urinalysis (i.e., positive nitrite or leukocyte esterase test on urine dipstick or >5 WBCs/hpf on urine microscopy). 17,18 Cultures from which more than 1 bacterial species were isolated were considered contaminated unless 1 or more was a true pathogen.…”
Section: Methodsmentioning
confidence: 99%
“…However, CRP has consistently demonstrated higher specificity than WBC count for SBI and IBI, often at the expense of a lower sensitivity. 2934 While Milcent et al reported the highest sensitivity of 77% (95% CI: 66–86) for detection of SBI with a cutoff value of 20 mg/L, 33 this sensitivity is still low for detection of bacterial infection.…”
Section: Are There New Diagnostic Tools That Can Be Incorporated Intomentioning
confidence: 99%
“…More recently, in the largest trial of its kind, Milcent et al 10 recruited over 2000 febrile infants less than 3 months of age presenting to the emergency department. They report an NLR of 0.1 for bacteraemia and bacterial meningitis in infants with a PCT of <0.3 ng/mL, demonstrating that a negative PCT markedly reduced the post-test probability of an IBI in a well-looking febrile infant.…”
Section: Indications and Limitationsmentioning
confidence: 99%
“…When compared with conventional markers of bacterial infection (CRP and neutrophils) in infants, PCT has better sensitivity and specificity for invasive infection (ie, bacteraemia and meningitis) than less invasive infections such as UTI and pneumonia 10. Milcent et al report that febrile infants with a raised PCT (>0.3 ng/mL) have a positive likelihood ratio of 4, suggesting that the likelihood of an IBI in such an infant is moderately raised 10. Furthermore, they report a sensitivity of a raised PCT level (>0.3 ng/mL) of 90%; for every 10 febrile infants with confirmed IBI, PCT alone would have correctly identified 9.…”
Section: Indications and Limitationsmentioning
confidence: 99%